2016
DOI: 10.1016/j.toxlet.2016.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Chronic exposure to trichloroethylene increases DNA methylation of the Ifng promoter in CD4+ T cells

Abstract: CD4+ T cells in female MRL+/+ mice exposed to solvent and water pollutant trichloroethylene (TCE) skew toward effector/memory CD4+ T cells, and demonstrate seemingly non-monotonic alterations in IFN-γ production. In the current study we examined the mechanism for this immunotoxicity using effector/memory and naïve CD4+ T cells isolated every 6 weeks during a 40 week exposure to TCE (0.5 mg/ml in drinking water). A time-dependent effect of TCE exposure on both Ifng gene expression and IFN-γ protein production w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…TRIM68 (Tripartite Motif Containing 68) is involved in immunity and cancer and has been shown to negatively regulate an antagonist of interferon gamma, interferon beta [19]. A time-dependent effect of TCE on interferon gamma gene expression and protein expression was observed in mice [9]. Also, an increase in interferon gamma has previously been reported as an effect of occupational exposure to TCE [20].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…TRIM68 (Tripartite Motif Containing 68) is involved in immunity and cancer and has been shown to negatively regulate an antagonist of interferon gamma, interferon beta [19]. A time-dependent effect of TCE on interferon gamma gene expression and protein expression was observed in mice [9]. Also, an increase in interferon gamma has previously been reported as an effect of occupational exposure to TCE [20].…”
Section: Discussionmentioning
confidence: 96%
“…The most significant and biologically relevant DVPs were found in genes CTNND2 (Catenin Delta 2), EFNB2 (Ephrin B2), CAP2 (Cyclase Associated Actin Cytoskeleton Regulatory Protein 2), and ZNF259 (Zinc Finger Protein ZPR1/259), which have all been related to cancer and autoimmune disease [15][16][17][18]. Also, almost all of the 25 genomewide significant DVPs were hypermethylated (Supplementary Table S1(J-M)) and, interestingly, this pattern was hypothesized in [9]. Perhaps increased variability of DNA CpG methylation may be precursor to changes in mean DNA CpG methylation?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the effects persisted after TCE was removed from the drinking water suggested that programming events played a role in disease pathology. Indeed TCE altered the DNA methylation profile of the IFN-γ promoter in mouse CD4 + T cells [63]. In a genome-wide DNA methylation and gene expression study, TCE exposure in vivo differentially methylated CpGs in regions that bind polycomb group proteins [64] whose function is to regulate T effector cell expansion and differentiation [65].…”
Section: Trichloroethylenementioning
confidence: 99%
“…A subsequent study, using targeted bisulfite next generation sequencing of amplicons generated on a Fluidigm Access Array, examined TCE- and time-dependent changes in DNA methylation associated with 16 functionally important genes in CD4 + T cells. TCE was found to increase gene-specific methylation variance in effector/memory CD4 + cells [ 6 ], and to induce a time-dependent cumulative increase in DNA methylation in the CpG sites of the promoter of the Ifng gene [ 39 ].…”
Section: Introductionmentioning
confidence: 99%